The Waterworks: A Parallax View of a Modern Gothic Tale - Theodora Tsimpouki; Maria Pirgerou (American Gothic Studies, 2025)
In his 1994 novel The Waterworks, E. L. Doctorow constructs a modern Gothic tale of horror in the heart of New York City at the end of the nineteenth century. Adopting Slavoj Žižek’s “parallax view,” this article contends that Dr. Sartorius’s gory, antagonistic obsession to defeat death constructs a nightmarish network of undead spectral “life” that escapes the ontological horizon delineated by the Symbolic and, at the same time, disrupts its social inscription, rendering visible fin de siècle societal antagonisms. The undead non-subjects whose materialization is contingent upon the blood and bone marrow of the children upon which they prey are used in this modern Gothic text as an exemplification of the unspeakable Real that is inscribed into the very fabric of capitalism.